Economic justification for quarantine status – the case study of 'Candidatus Liberibacter solanacearum' in the European Union. (7th January 2013) - Soliman, T.; Mourits, M. C. M.; Oude Lansink, A. G. J. M.; van der Werf, W.
Abstract : International agreements on plant health and trade require that regulating a pest should be justified by economic impact assessment. Economic impact assessments are usually qualitative, weakening the objective and transparency of the regulation decision. This study assessed the potential economic impacts of the invasion of the plant pathogenic bacterium ' Candidatus Liberibacter solanacearum' into the European Union in order to economically justify a decision on its quarantine status. Direct economic impacts resulting from yield loss in potato and tomato were computed using partial budgeting at a regional scale, while total economic impacts on the potato and tomato markets were computed using partial equilibrium modelling at the EU scale. Annual direct impacts at the most likely infestation level were estimated at €222 m for the whole EU. Uncertainty analysis showed a distribution of foreseeable annual impacts with a 5th percentile of €192 m, and a 95th percentile of €512 m. Increased market prices of potato and tomato resulting from reduced supply were found to increase profits for non‐infested producers and to compensate in part for the production losses of infested producers, with consumers paying for this mitigation of impacts on producers. The expected negative impact on societal welfare at the most likely infestation level is less than the estimated direct impacts, viz. €114 m/year. The potential economic impacts of ' Ca . L. solanacearum' in the European Union are demonstrably of major importance. Therefore, a decision to categorize this organism as a quarantine pest is supported.